Contaminação por protozoários potencialmente patogêni-cos ao homem na água de diferentes pontos da Laguna dos Patos, Rio Grande, RS - Falchi, Ricardo Luiz Ricci (2006)
In countries in development, one of the main causes of diseases is the contamination of the water due to the deficiency of the sanitary sewerage system. Rio Grande city, situated in the South of Rio Grande do Sul, as the majority of the Brazilian cities also presents limitations in the collection and treatment of the cloacal sewer. This deficiency makes that part of the residues of the population be eliminated directly in the Patos Lagoon, which acquits a important role in the fishing activity, besides being used as local for washing, in the summer months, by the population which lives around. This study had as objectives to investigate the presence of pathogenic parasites to the man and parasites that are indicator of fecal contamination water samples gathered in different parts of the Patos Lagoon, Rio Grande, RS. In the period between January and December of 2005, it was gathered, monthly, samples of 500mL of water in 12 different parts of the Lagoon. The samples were filtered through a membrane of acetate of cellulose (0,45), under a negative pressure for the material retention. After the material elution, through the Tween 80 solution to 0, 1%, the material was concentrated by centrifugation in 1500 rpm, during 15 minutes. For the initial research of protozoa, it was achieved the direct exam in breezy of the material, as well as the material concentrated by the centrifugal-flotation technique in solution of sulfate of zinc. For the research of oocysts of Cryptosporidium spp., they were achieved concurrently the techniques of concentration centrifugal-flotation of Sheather and centrifugal-sedimentation by formol ether, with the posterior coloration with the Kinyoun technique. For the research of free-living amoebas, it was made the culture of one aliquot of each water sample in non-nutrient agar inoculated with inactive Escherichia coli . Aliquots originated of the eluted material from the membrane and of the culture were ruddy by trichrome, for the diagnosis of protozoa cysts. In the gathering places of the samples it was sized pH, saltiness and water temperature. The research of total coliforms and Escherichia coli was achieved by the technique of multiple tubes. In the analysis of the 12 parts, during the 12 months of water gathering, it was observed that 91,7% were infected with protozoa that can infect human beings; Cryptosporidium spp. (16,7%), Acanthamoeba spp. (91,7%), Naegleria spp. (25%) and Entamoeba histolytica/Entamoeba dispar (8,3). Total coliforms (more than 5.000/100mL) and Escherichia coli (more than 1.000/100mL) were secluded in all the harvested samples, showing water contamination by cloacal sewer. The temperature, the saltiness and water pH, do not influenced in the detection do protozoa, except for Acanthamoeba spp. That presented bigger frequency when the water saltiness was under or equal 0,6% (p < 0,05). The presence of organic substance in the closeness of the places of samples gathering influenced in the detection of protozoa in general, as well as the creation of animals for the detection of Naegleria spp. (p < 0.05). The observation of water contamination for pathogenic parasites to man and the indications of fecal contamination, suggest better action of sanitary planning, as well as preventive and educative steps in order to avoid the human infection.